Case Report: Transformation From Non-Small Cell Lung Cancer to Small Cell Lung Cancer During Anti-PD-1 Therapy: A Report of Two Cases - Shen, Qian; Qu, Jingjing; Sheng, Lingyan; Gao, Qiqi; Zhou, Jianying (Frontiers in Oncology, 2021)
Background Histological transformation of lung cancer to small cell lung cancer (SCLC) is uncommon. It is a small subset of the possible resistance mechanisms, even in epidermal growth factor receptor (EGFR)-mutated non-small cell lung cancer treated with EGFR-tyrosine kinase inhibitors. Reports on programmed cell death-1 (PD-1) inhibitors are rare. We report two cases of lung squamous carcinomas that transformed to SCLC during anti-PD-1 therapy, and present a detailed description of histological examination of the pre-and post-transformation tissues, hitherto absent from reports on the topic. Case Presentation Case 1: A 69-year-old man was diagnosed with stage IVa squamous cell carcinoma of the lung. He had a programmed cell death-ligand 1 tumor proportion score ≥50%. He achieved partial response after four cycles of sintilimab as first-line treatment. However, sintilimab was discontinued because of severe decrease in hemoglobin levels and platelet counts. Moreover, the occurrence of pleural effusion favored disease progression. Interestingly, bone marrow puncture and biopsy showed transformation to SCLC. Case 2: A 71-year-old man diagnosed with stage IIIa lung squamous cell carcinoma received neoadjuvant chemotherapy, underwent radical surgery, and finally received adjuvant chemotherapy. Five months later, he presented with tumor recurrence. He was treated with nivolumab, though disease progression was observed after four cycles. Notably, a subsequent computed tomography-guided biopsy showed SCLC. Conclusion Phenotypic transformation to SCLC is a potential mechanism of resistance to immunotherapy in squamous cell carcinomas of the lung. Disease progression should prompt re-biopsy to diagnose potential histological changes to assess the requirement for change in treatment.